BERADAPTASI DENGAN PERUBAHAN PASAR DALAM STRATEGI BERSAING YANG FLEKSIBEL DAN DINAMIS - Oktavia; Athifah Dzakirah, Nur; Alifa Bintang Defana, Muhammad; Noviyanti, Indah (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This research aims to identify flexible and dynamic business strategies in adapting to market changes. The research method used is qualitative descriptive with a literature study approach to understand ideas and theories relevant to the research topic. The analysis employed is descriptive analysis, which analyzes the data by describing or presenting the information without attempting to draw broad conclusion or generalization. Furthermore, Flexible and dynamic competitive strategies allow companies to not only adapt to market changes, but also take advantage of these changes to increase intelligence and business efficiency. These constraints include changes in the market, which are often accelerating, and companies respond slowly to market changes, thereby reducing adaptation and competition. A flexible and dynamic competitive strategy in changing markets would demonstrate that companies were able to successfully adapt to market changes, increase their capacity and achieve business success. This research is expected to help society, especially businesses, to determine flexible and dynamic strategies to adapt to changes in a market